OTOMATISASI PEKERJAAN GURU BERBASIS AUTOCRAT: MODEL PENDIDIKAN DAN PELATIHAN BERDASARKAN PENDEKATAN KONEKTIVISME - Filianti, Filianti; Yuniarsih, Tjutju; Meilani, Rini Intansari (Jurnal Pendidikan Manajemen Perkantoran (JPManper), 2022)
In addition to having an obligation to teach students in the classroom, teachers also has obligation to carry out administrative tasks to involve students outside the classroom. If implemented using conventional methods, this will complicate the effectiveness of the teacher's work. The purpose of this study is to develop a connectivity-based education and training model related to the automation of teacher work in the digital era through the use of the Autocrat Add-on in Google Sheets. The development of the model began by conducting a needs analysis of 59 teacher respondents from various parts of Indonesia to review the technical problems being faced, the need for problem-solving solutions, an initial understanding of the work support tools of the Autocrat Add-on and the expected output from the use of the Autocrat Add-on. The findings in this study can be used as a basis for carrying out teacher professional development activities in the digital era, especially related to the automation of teachers' work through the use of Ad-on Autocrats in order to make their work more efficient and effective.